2009
DOI: 10.1002/aic.11987
|View full text |Cite
|
Sign up to set email alerts
|

Influence of elevated pressure and particle lyophobicity on hydrodynamics and gas–liquid mass transfer in slurry bubble columns

Abstract: This article reports on the influence of elevated pressure and catalyst particle lyophobicity at particle concentrations up to 3 vol % on the hydrodynamics and the gasto-liquid mass transfer in a slurry bubble column. The study was done with demineralized water (aqueous phase) and Isopar-M oil (organic phase) slurries in a 0.15 m internal diameter bubble column operated at pressures ranging from 0.1 to 1.3 MPa. The overall gas hold-up, the flow regime transition point, the average large bubble diameter, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 41 publications
0
19
1
Order By: Relevance
“…This decrease of the liquid axial dispersion coefficient with pressure disagrees with other publications (Chilekar et al, 2010;Holcombe et al, 1983;Houzelot et al, 1983;Sangnimnuan et al, 1984;Therning and Rasmuson, 2001;Wilkinson et al, 1993). Sangnimnuan et al (1984) do not observe any effect of pressure in the range 4.5 -15 MPa in the homogeneous regime, as for their gas holdup.…”
Section: Figurecontrasting
confidence: 83%
See 2 more Smart Citations
“…This decrease of the liquid axial dispersion coefficient with pressure disagrees with other publications (Chilekar et al, 2010;Holcombe et al, 1983;Houzelot et al, 1983;Sangnimnuan et al, 1984;Therning and Rasmuson, 2001;Wilkinson et al, 1993). Sangnimnuan et al (1984) do not observe any effect of pressure in the range 4.5 -15 MPa in the homogeneous regime, as for their gas holdup.…”
Section: Figurecontrasting
confidence: 83%
“…However, they observe an increase of the liquid axial dispersion coefficient with pressure despite the decrease of bubble size. This is also the case for Chilekar et al (2010) who observed that, in fact, liquid recirculation increases when increasing pressure. Therning and Rasmuson (2001) also observed the increase of axial dispersion coefficient with a packed column.…”
Section: Figurementioning
confidence: 55%
See 1 more Smart Citation
“…It is generally admitted that-in the homogeneous flow regime-d b increases [156] and, after the transition, "coalescence induced" bubbles appear, whereas the contribution of the "non-coalescence induced" bubbles remain constant [18]. Some authors reported an increase in d b with superficial gas velocity, both in the homogeneous and heterogeneous flow regimes [35,38,85,87,127,183,[232][233][234][235][236][237][238][239], while other authors reported no effect of U G over d b [188,240] and some others reported a decrease in the bubble size [241]. In the literature, both unimodal [239] and bimodal [242][243][244][245] BSD have been found depending on the gas sparger design and operating conditions.…”
Section: Superficial Gas Velocitymentioning
confidence: 99%
“…Also Chaumat et al studied the mass transfer in a bubble column with water and organic media in industrial conditions and the connection with mass transfer and hydrodynamics [9]. Schaaf et al and Chilekar et al studied gas-liquid mass transfer in a 0.15 m diameter slurry bubble column with a pressure from 0.1 to 1.3 MPa, and presented a correlation of mass transfer coefficient [10,11]. Lemoine et al developed the empirical and neural network correlations for predicting gas holdups, volumetric liquid-side mass transfer coefficients, Sauter mean bubble diameters, gas-liquid interfacial areas and liquid-side mass transfer coefficients for total, small and large gas bubbles in BCRs and SBCRs [12].…”
Section: Introductionmentioning
confidence: 99%